Molecular mechanisms governing the progression of nephritis in lupus prone mice and human lupus patients - Daamen, Andrea R.; Wang, Hongyang; Bachali, Prathyusha; Shen, Nan; Kingsmore, Kathryn M.; Robl, Robert D.; Grammer, Amrie C.; Fu, Shu Man; Lipsky, Peter E. (Frontiers in Immunology, 2023)
Pathologic inflammation is a major driver of kidney damage in lupus nephritis (LN), but the immune mechanisms of disease progression and risk factors for end organ damage are poorly understood. To characterize molecular profiles through the development of LN, we carried out gene expression analysis of microdissected kidneys from lupus-prone NZM2328 mice. We identified a continuum of inflammatory processes associated with the progression from acute inflammatory to chronic destructive disease. We examined male mice and the congenic NZM2328.R27 strain as a means to define mechanisms associated with resistance to chronic nephritis. Male mice exhibited minimal immune infiltration resulting in non-progressive renal pathology. The molecular profiles of R27 mice were enriched for immunoregulatory gene signatures in conjunction with enrichment of kidney tubule cells indicative of resistance to cellular damage. The gene expression profiles of human LN were similar to those noted in the NZM2328 mouse suggesting comparable stages of LN progression.